Environmental adaptation and vertical dissemination of ESBL‐/pAmpC‐producing Escherichia coli in an integrated broiler production chain in the absence of an antibiotic treatment. Issue 6 (17th January 2018) - Projahn, Michaela; Daehre, Katrin; Semmler, Torsten; Guenther, Sebastian; Roesler, Uwe; Friese, Anika
Summary: High prevalence numbers of extended‐spectrum beta‐lactamase‐ (ESBL‐)/plasmid‐mediated AmpC beta‐lactamase‐ (pAmpC‐) producing Escherichia coli in broiler chicken and their distribution along the broiler production chain is an ongoing problem in food production. We, therefore, investigated resistant isolates along the broiler production chain to determine whether there is a constantly occurring direct vertical transmission of the ESBL‐/pAmpC‐producing E. coli from the parent flocks to their offspring or not. We, furthermore, analysed the isolates concerning the occurrence of virulence factors and their ability to form biofilms to estimate their potential to effectively colonize broiler chickens and/or persist and survive in the environment of the broiler production facilities. Using whole genome sequencing, we could show that ESBL‐/pAmpC‐producing E. coli were likely transferred in a step‐wise process along the broiler production chain but not directly from the parent flock to the fattening flock with every single batch of offspring chickens. Additionally, resistant E. coli strains showing an extraintestinal pathogenic genotype as well as high numbers of virulence‐associated genes including the production of curli fibres and cellulose have high capabilities to persist and spread in the broiler production chain. Abstract : Antibiotic resistant Escherichia coli are widespread in broiler chickens and increasingly found in healthy chickens which were never treated by any antibiotics. Therefore, the spread of ESBL‐/pAmpC‐producing E. coli in the broiler production and the colonization of broiler chickens seems to be supported by factors other than mere antimicrobial selection pressure. Our study provides further insights into the evolution and the virulence properties of ESBL‐/pAmpC‐producing E. coli as well as the vertical transmission processes along the production chain.